FED-BATCH FERMENTATION ON PRODUCTION OF A BIODEGRADABLE PLASTIC POLY(3-HYROXYBUTYRATE) FROM OLEIC ACID - Djamaan, Akmal; Majid, Mohammed Isa Abdul; Noor, Mohd. Azizan Mohd. (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2003)
A fed-batch fermentation with a purpose to increase the production of biodegradable plastic poly(3-hydroxybutyrate), P(3HB), from oleic acid by Erwinia sp. USMI-20 has been carried out. Fermentation was conducted in a conical flask in an incubator rotary shaker at temperature of 30 oC, agitation of 200 rpm for 66 hours. At first stage of fermentation process in a mineral medium, 5 ml of oleic acid as the sole carbon source was used while feeding were done with 2.5 ml of oleic acid at 30, 42 and 54 hours of cultivation. Sampels were collected every 4 hours until 18 hours of cultivation and every 6 hours until 66 hours of cultivation. P(3HB) production was characterized based on the increase of dry cells, polymer content, polymer concentration and the amount of oleic acid and ammonium remaining in the culture. Results showed that by using fed-batch technique Erwinia sp. USMI-20 could produce P(3HB) with a maximum polymer content of 52 % of the dry cell weight, the concentration of polymer of 2.8 g/l, a dry cell weight of 5.4 g/l.Keywords : Fed-batch, biodegradable plastic, poly(3-hydroxybutyrate, oleic acid).